PHK SEPIHAK: PROSEDUR, HAK PEKERJA, DAN PENYESELAIANNYA SECARA HUKUM - Abd Jalil, Moh Fadhel; Fatriani, Fenny (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2025)
Unilateral Termination of Employment (PHK) is one of the problems that often arise in industrial relations in Indonesia. Unilateral layoffs occur when one of the parties, both employers and workers, terminates the employment relationship without going through a mutual agreement or without a valid reason in accordance with the provisions of the law. The unilateral layoff process is regulated in Law Number 13 of 2003 concerning Manpower, which provides protection to workers, both in its implementation procedures and the rights that must be given. Even so, the implementation of unilateral layoffs often causes disputes between workers and employers. Therefore, the resolution of unilateral layoff disputes can be carried out through mediation, conciliation, or arbitration, which is regulated in Law No. 2 of 2004 concerning Industrial Relations Dispute Resolution. . This study aims to examine the procedure for unilateral layoffs, workers' rights in unilateral layoffs, and the mechanism for resolving unilateral layoff disputes in accordance with applicable laws in Indonesia.